Assessment of Cardiovascular Autonomic Function in Patients with Headache in A Tertiary Care Centre: A Prospective Study - Dr. Netla. Saranya; Dr. Murali Mohan Reddy; Dr S. Latha (International Journal of Pharma and Bio Sciences, 2023)
Migraine is a headache with hypersensitivity to sensory stimuli. It was the 7th most common disability as per the World health organization (WHO) with autonomic dysfunction. The prevalence is highest among persons between 35 to 45 years. Only a few studies have investigated the potential of cardiac autonomic dysfunction in India due to migraine, cluster, and tension headaches. This study investigated cardiac autonomic function by analyzing heart rate and blood pressure variability. A better understanding may provide insight into central autonomic regulation, help frame appropriate management guidelines, and provide an opportunity to identify drugs targeting the autonomic system. The study aims to assess the pattern of cardiovascular autonomic function tests (AFT) in patients with three types of headaches, including cluster headache (C.H.), tension headache (T.H.), and migraine. This study was done in the Department of Physiology, Sri Lakshmi Narayana Institute of Medical Sciences, Pondicherry, Tamil Nadu, India, from Oct 2021 to Jan 2022, after getting approval from the institutional ethics committee. Ninety patients with a single type of either of 3 headaches were assessed. Patients were divided into three Groups-Group M, Group T.H., and Group CH. Results showed that most patients were 30-39 years old. There were no significant differences in H.R. and B.P. during sitting or rest, standing, Valsalva manoeuvre, and isometric handgrip (I.H.G.) in the 3 groups outside the attack. Systolic B.P. was found to be less during migraine in the M group, and Diastolic B.P. was more in patients during an attack in the C.H. group. The results indicate no sympathetic abnormality in tension headaches. But sympathetic hypofunction has activated the trigeminovascular system causing headaches in migraine patients.